A fluororesin microporous foam material and preparation method thereof

Through the melt blending and irradiation crosslinking technology of modified porous SiO2 and PVDF and P(VDF-HFP) copolymers, the problems of poor melt strength and poor cell structure of PVDF type fluororesin foaming materials during processing were solved, and fluororesin microporous foaming materials with uniform cell structure and high magnification were prepared, which expanded its application in high-performance applications.

CN118994701BActive Publication Date: 2025-03-14ZHEJIANG XINHENGTAI ADVANCED MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411491339.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-03-14
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

During the processing process, the existing PVDF type fluororesin foaming materials have problems such as poor melt strength, limited foaming ratio and poor cell structure, which limits their application and development in the fields of aerospace, semiconductors, and medical care.

Method used

Modified SiO2 of surface-modified epoxy groups was obtained by mixing porous SiO2 with silane coupling agent in xylene, ultrasonic mixing and reflux under N2 atmosphere, and melt blending with polyethylene grafted maleic anhydride to prepare modified SiO2 of surface-grafted polyethylene. Then, the fluororesin microporous foaming material is melt blended with homopolymer PVDF and P(VDF-HFP) copolymer, irradiation crosslinking and high-pressure and low-temperature infiltration, and finally the fluororesin microporous foaming material is prepared by supercritical fluid foaming.

Benefits of technology

The gas solubility and melt strength of the foaming precursor are improved, and a fluororesin microporous foaming material with a uniform cell structure and high magnification is prepared, which improves the buffering and insulation performance and application range of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994701B_ABST
    Figure CN118994701B_ABST
Patent Text Reader

Abstract

The invention discloses a fluororesin microporous foam material and a preparation method thereof. The preparation of the foam material comprises the following steps: preparation of modified porous SiO2 and melt blending thereof with homopolymerized PVDF and P (VDF-HFP) copolymer to prepare a foaming precursor, and then subjecting the foaming precursor to irradiation cross-linking and high-pressure low-temperature infiltration, and finally foaming with a supercritical fluid. The foaming material comprises 3-15 parts by weight of modified SiO2, 5-20 parts by weight of homopolymerized PVDF, and 60-90 parts by weight of P (VDF-HFP) copolymer. By adding modified SiO2, high solubility in supercritical fluid is achieved, the diffusion path is shortened, homopolymerized PVDF and P (VDF-HFP) copolymer are melt blended to broaden the foaming window, irradiation cross-linking improves melt strength, and a high-ratio fluororesin microporous foam material with a uniform pore structure is prepared, the foaming material has excellent performance, a simple preparation method, and high production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high molecular polymers, in particular to a fluororesin microporous foaming material and a preparation method thereof. Background Art

[0002] Polyvinylidene fluoride (PVDF) is a typical semi-crystalline fluororesin polymer with outstanding thermal stability, corrosion resistance, non-flammability and hydrophobicity, excellent weather resistance and mechanical strength, easy processing and other characteristics, and has a wide range of industrial uses. Foaming is an important means to expand the properties and application range of polymers. The preparation of PVDF-based foaming materials with high foaming ratios through foaming technology greatly improves the cushioning and thermal insulation properties of PVDF while maintaining its original excellent properties, expanding its application in aerospace, semiconductor, medical and other fields.

[0003] However, due to its high processing temperature, conventional chemical foaming agents are not applicable, and there are problems such as environmental protection. Therefore, supercritical fluid foaming can be used as an effective foaming method to prepare PVDF-based foaming materials. However, conventional PVDF has poor melt strength, limited foaming rate, and poor pore structure, which limits the application and development of PVDF-based fluororesin foaming materials. Summary of the invention

[0004] The purpose of the present invention is to provide a fluororesin microporous foam material and a preparation method thereof in view of the deficiencies in the prior art, which is specifically achieved by the following technical scheme.

[0005] A method for preparing a fluororesin microporous foam material comprises the following steps:

[0006] (1) Porous SiO2 and silane coupling agent are added to xylene and mixed, which may be ultrasonically mixed and refluxed under N2 atmosphere. After the reaction is completed, the unreacted silane coupling agent is removed to obtain SiO2 with surface modified epoxy groups, which is then melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. Preferably, the weight ratio of the porous SiO2, silane coupling agent and polyethylene grafted maleic anhydride is 1:(1-3):(3-6). The silane coupling agent is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane. Furthermore, after the reaction of porous SiO2 and silane coupling agent is completed, the crude product is filtered and washed with dichloromethane to remove the unreacted silane coupling agent.

[0007] (2) The modified SiO2, homopolymer PVDF and P(VDF-HFP) copolymer are melt-blended to prepare a foaming precursor. The P(VDF-HFP) is a vinylidene fluoride-hexafluoropropylene copolymer.

[0008] (3) The foaming precursor is subjected to irradiation cross-linking to cause a cross-linking reaction between the modified SiO2 and PVDF molecular chains, and the irradiation dose is preferably 5-80 KGy.

[0009] (4) The irradiated foaming precursor is placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 15-25 MPa and a temperature of 120-140°C. After a certain period of time, the temperature is reduced to below 100°C, and then the pressure is slowly released to room temperature. Preferably, the foaming precursor is subjected to high-pressure and low-temperature infiltration for 4-10 hours.

[0010] (5) The foaming precursor obtained in step (4) is subjected to supercritical fluid foaming. The specific foaming conditions are preferably: the foaming precursor is placed in a mold foaming cavity, the temperature is controlled at 140-160° C., the pressure of the injected supercritical fluid is 8-15 MPa, the temperature and pressure are kept constant for 1-4 h, and then the pressure is released to normal pressure, and the mold is opened to obtain a fluororesin microporous foam material. The supercritical fluid is at least one of supercritical carbon dioxide and supercritical nitrogen.

[0011] The foaming material comprises the following components in parts by weight: 3-15 parts of modified SiO2, 5-20 parts of homopolymer PVDF, and 60-90 parts of P (VDF-HFP) copolymer. In the P (VDF-HFP) copolymer, the weight percentage of HFP is 4%-20%.

[0012] The fluororesin microporous foam material provided by the present invention is obtained by adopting the above-mentioned preparation method.

[0013] The advantages of the present invention are:

[0014] 1. By preparing modified porous SiO2, the gas solubility of the foaming precursor is improved, providing sufficient power for the subsequent cell nucleation and cell growth; shortening the gas diffusion path, reducing the infiltration time, and improving the high-pressure infiltration efficiency. At the same time, the modified porous SiO2 can be used as a heterogeneous nucleation point to improve the nucleation efficiency of the cell nucleus and increase the cell density.

[0015] 2. The melt blending of homopolymer PVDF and P (VDF-HFP) copolymer can broaden the melting range of the blend, broaden the foaming window, reduce the sensitivity of the foaming ratio to temperature, and prepare a more uniform foaming material.

[0016] 3. Radiation cross-linking can cause the polyethylene molecular chains on the surface of porous SiO2 to cross-link with the PVDF molecular chains to form an integrated structure, while improving the melt strength of the foaming precursor and preparing a uniform pore structure, which can effectively inhibit the shrinkage of PVDF-based foaming materials after foaming. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Attached Figure 1 3 is a scanning electron microscope image of the foamed material prepared in Example 4. DETAILED DESCRIPTION

[0018] This embodiment is implemented under the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. Unless otherwise specified, the materials used are commercially available conventional products. The parts of raw materials used in all the following embodiments and comparative examples are parts by weight.

[0019] The homopolymer PVDF is DE 6-4 PVDF produced by Zhejiang Juhua or Flurine ® FL2006 PVDF produced by Zhejiang Funolin Chemical New Materials Co., Ltd.

[0020] P(VDF-HFP) copolymer was purchased from Solef 11010.

[0021] Example 1

[0022] Porous SiO2 and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted γ-(2,3-epoxypropoxy)propyltrimethoxysilane is washed with dichloromethane to remove the SiO2 with epoxy groups modified on the surface. Then, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with polyethylene grafted on the surface. The weight ratio of porous SiO2, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:2:3.

[0023] 3 parts of modified SiO2, 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0024] The foaming precursor is irradiated and cross-linked at a radiation dose of 30 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0025] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0026] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical carbon dioxide injected was 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0027] Example 2

[0028] Porous SiO2 and 3-(2,3-epoxypropoxy)propyltriethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted 3-(2,3-epoxypropoxy)propyltriethoxysilane is washed with dichloromethane to obtain SiO2 with surface modified epoxy groups. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. The weight ratio of porous SiO2, 3-(2,3-epoxypropoxy)propyltriethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:1:3.

[0029] 5 parts of modified SiO2, 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0030] The foaming precursor is irradiated and cross-linked at a radiation dose of 30 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0031] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0032] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical nitrogen was injected at 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0033] Example 3

[0034] Porous SiO2 and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane is washed with dichloromethane to obtain SiO2 with surface modified epoxy groups. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. The weight ratio of porous SiO2, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:3:3.

[0035] 10 parts of modified SiO2, 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0036] The foaming precursor is irradiated and cross-linked at a radiation dose of 30 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0037] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0038] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical nitrogen was injected at 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0039] Example 4

[0040] Porous SiO2 and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane is washed with dichloromethane to obtain SiO2 with surface modified epoxy groups. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. The weight ratio of porous SiO2, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:3:6.

[0041] 15 parts of modified SiO2, 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0042] The foaming precursor is irradiated and cross-linked at a radiation dose of 30 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0043] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0044] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical nitrogen was injected at 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0045] Example 5

[0046] Porous SiO2 and 3-(2,3-epoxypropoxy)propyltriethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted 3-(2,3-epoxypropoxy)propyltriethoxysilane is washed with dichloromethane to remove the SiO2 with epoxy groups modified on the surface. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with polyethylene grafted on the surface. The weight ratio of porous SiO2, 3-(2,3-epoxypropoxy)propyltriethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:3:4.

[0047] 5 parts of modified SiO2, 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0048] The foaming precursor is irradiated and cross-linked at a radiation dose of 50 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0049] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0050] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical nitrogen was injected at 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0051] Example 6

[0052] Porous SiO2 and silane coupling agent are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted silane coupling agent is washed with dichloromethane to obtain SiO2 with surface modified epoxy groups. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. The weight ratio of porous SiO2, silane coupling agent and polyethylene grafted maleic anhydride in this embodiment is 1:2:6. The silane coupling agent is composed of 3-(2,3-epoxypropoxy)propyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:1.

[0053] 8 parts of modified SiO2, 20 parts of homopolymer PVDF and 60 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0054] The foaming precursor is irradiated and cross-linked at a radiation dose of 5 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0055] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 15 MPa and a temperature of 140°C. After infiltration for 6 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0056] The obtained foaming precursor is placed in a molded foaming cavity, the temperature is controlled at 140°C, the pressure of the injected supercritical fluid is 15 MPa, the supercritical fluid is a mixture of supercritical carbon dioxide and supercritical nitrogen, the temperature and pressure are maintained constant for 1 h, then the pressure is released to normal pressure, and the mold is opened to obtain the foaming material.

[0057] Example 7

[0058] Porous SiO2 and silane coupling agent are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted silane coupling agent is washed with dichloromethane to obtain SiO2 with surface modified epoxy groups. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene. The weight ratio of porous SiO2, silane coupling agent and polyethylene grafted maleic anhydride in this embodiment is 1:1:6. The silane coupling agent is composed of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane in a mass ratio of 2:1.

[0059] 12 parts of modified SiO2, 5 parts of homopolymer PVDF and 70 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0060] The foaming precursor is irradiated and cross-linked at a radiation dose of 80 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0061] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 25 MPa and a temperature of 130°C. After infiltration for 4 h, the temperature was reduced to 90°C and then slowly released to room temperature.

[0062] The obtained foaming precursor is placed in a molded foaming cavity, the temperature is controlled at 160°C, the pressure of the injected supercritical fluid is 8 MPa, the supercritical fluid is a mixture of supercritical carbon dioxide and supercritical nitrogen, the temperature and pressure are kept constant for 4 hours, then the pressure is released to normal pressure, and the mold is opened to obtain the foaming material.

[0063] Example 8

[0064] Porous SiO2 and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are added to xylene and ultrasonically mixed until uniform, refluxed under N2 atmosphere, and filtered to obtain a crude product after the reaction is completed. The unreacted γ-(2,3-epoxypropoxy)propyltrimethoxysilane is washed with dichloromethane to remove the SiO2 with epoxy groups modified on the surface. Subsequently, it is melt-blended with polyethylene grafted maleic anhydride to prepare modified SiO2 with polyethylene grafted on the surface. The weight ratio of porous SiO2, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and polyethylene grafted maleic anhydride in this embodiment is 1:2:5.

[0065] 9 parts of modified SiO2, 15 parts of homopolymer PVDF and 80 parts of P (VDF-HFP) copolymer were melt blended to prepare a foaming precursor.

[0066] The foaming precursor is irradiated and cross-linked at a radiation dose of 65 Kgy, so that a cross-linking reaction occurs between the polyethylene molecular chains and the PVDF molecular chains on the surface of the modified SiO2.

[0067] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 18 MPa and a temperature of 135°C. After infiltration for 10 h, the temperature was reduced to 70°C and then slowly released to room temperature.

[0068] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 155°C, the pressure of supercritical carbon dioxide injected was 10 MPa, the temperature and pressure were kept constant for 3 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0069] Comparative Example 1

[0070] The foaming precursor was prepared by melt blending 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer.

[0071] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical carbon dioxide injected was 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0072] The difference from Example 1 is that modified SiO2 is not used as the raw material and there is no irradiation step in the preparation method.

[0073] Comparative Example 2

[0074] The foaming precursor was prepared by melt blending 10 parts of homopolymer PVDF and 90 parts of P (VDF-HFP) copolymer.

[0075] The foaming precursor was irradiated and cross-linked, and the irradiation dose was 30 Kgy.

[0076] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0077] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical carbon dioxide injected was 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0078] The difference from Example 1 is that no modified SiO2 is added to the raw materials.

[0079] Comparative Example 3

[0080] The preparation of modified SiO2 is the same as in Example 1.

[0081] The foaming precursor was prepared by melt blending 3 parts of modified SiO2 and 100 parts of P (VDF-HFP) copolymer.

[0082] The foaming precursor was irradiated and cross-linked at a radiation dose of 30 Kgy, so that a cross-linking reaction occurred between the polyethylene molecular chains and the P(VDF-HFP) molecular chains on the surface of the modified SiO2.

[0083] The irradiated foaming precursor was placed in a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 20 MPa and a temperature of 120°C. After infiltration for 8 h, the temperature was reduced to 80°C and then slowly released to room temperature.

[0084] The obtained foaming precursor was placed in a molded foaming cavity, the temperature was controlled at 150°C, the pressure of supercritical carbon dioxide injected was 12 MPa, the temperature and pressure were kept constant for 2 h, then the pressure was released to normal pressure, and the mold was opened to obtain the foaming material.

[0085] The difference from Example 1 is that no homopolymer PVDF is added to the raw material, and only P (VDF-HFP) copolymer is used.

[0086] Performance Testing

[0087] Table 1 Raw material weight parts and irradiation doses used in Examples 1 to 5 and Comparative Examples 1 to 3

[0088]

[0089] The foaming materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested for various properties according to the following standards, and the test was repeated three times. The test results are shown in Table 2. The foaming materials were tested using the following methods and conditions:

[0090] Density: Tested according to GB / T 6343;

[0091] Dimensional shrinkage: According to standard GB / T 8811, -55℃~70℃ test;

[0092] Cell size: The cross section of the foamed material was photographed using a scanning electron microscope, and the diameters of 200 cells were counted to obtain the average diameter.

[0093] Table 2 Parameters of foamed materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3

[0094]

[0095] It can be seen from Examples 1 to 4 that the content of modified SiO2 affects the cell size and size shrinkage rate. The higher the content of modified SiO2, the smaller the cell diameter and size shrinkage rate. This is because modified SiO2 increases the gas solubility, provides sufficient power for cell nucleation, and can also serve as a heterogeneous nucleation point to promote the formation of cell nuclei, increase cell density, and reduce cell diameter. Figure 1 3 is a scanning electron microscope image of the foamed material prepared in Example 4.

[0096] It can be seen from Examples 2 and 5 that the greater the irradiation dose, the smaller the cell diameter and size shrinkage rate, but the higher the foaming density.

[0097] The difference between Comparative Example 1 and Example 1 is that modified SiO2 is not used as the raw material, and there is no irradiation step in the preparation method. The results show that its pore size is twice that of Example 1, and the dimensional shrinkage rate is more than 3 times that of the example. The pore walls of large pores are thinner and the supporting force is weak, resulting in a worse dimensional shrinkage rate of the material.

[0098] The difference between Comparative Example 2 and Example 1 is that no modified SiO2 is added. The results show that its pore diameter is much larger than that of Example 1, and the dimensional shrinkage rate is higher.

[0099] The difference between Comparative Example 3 and Example 1 is that no homopolymer PVDF is added to the raw materials, the pore diameter is larger than that of Example 1, and the dimensional shrinkage rate is higher.

[0100] The present invention adopts a variety of measures such as adding modified porous SiO2 to achieve high solubility in supercritical fluid, shortening the diffusion path, melt blending homopolymer PVDF and P (VDF-HFP) copolymer to broaden the foaming window, and irradiation cross-linking to improve melt strength, thereby preparing a high-ratio fluororesin microporous foam material with a uniform pore structure. The foam material has excellent performance, a simple preparation method and high production efficiency.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a fluororesin microporous foam material, characterized in that: The following steps are involved: (1) adding porous SiO2 and a silane coupling agent into xylene and mixing them evenly, refluxing under a N2 atmosphere, removing the unreacted silane coupling agent after the reaction is completed, obtaining SiO2 with surface modified epoxy groups, and then melt blending with polyethylene grafted maleic anhydride to prepare modified SiO2 with surface grafted polyethylene; The silane coupling agent is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; (2) melt blending the modified SiO2, homopolymer PVDF and P(VDF-HFP) copolymer to prepare a foaming precursor; (3) irradiating and cross-linking the foaming precursor to cause a cross-linking reaction between the modified SiO2 and PVDF molecular chains; (4) placing the irradiated foaming precursor into a high-pressure chamber for high-pressure and low-temperature infiltration at a pressure of 15-25 MPa and a temperature of 120-140°C. After a certain period of time, the temperature is reduced to below 100°C, and then the pressure is slowly released to room temperature; (5) subjecting the foaming precursor obtained in step (4) to supercritical fluid foaming to obtain a fluororesin microporous foam material; The foaming material comprises the following components in parts by weight: 3-15 parts of modified SiO2, 5-20 parts of homopolymer PVDF, and 60-90 parts of P (VDF-HFP) copolymer.

2. The preparation method according to claim 1, characterized in that: In the P (VDF-HFP) copolymer, the weight percentage of HFP is 4%-20%.

3. The preparation method according to claim 1, characterized in that: The weight ratio of the porous SiO2, silane coupling agent and polyethylene grafted maleic anhydride in step (1) is 1:(1-3):(3-6).

4. The preparation method according to claim 1, characterized in that: After the reaction between the porous SiO2 and the silane coupling agent in step (1) is completed, the crude product is filtered out and washed with dichloromethane to remove the incompletely reacted silane coupling agent.

5. The preparation method according to claim 1, characterized in that: The irradiation dose in step (3) is 5-80 KGy.

6. The preparation method according to claim 1, characterized in that: In step (4), the foaming precursor is subjected to high pressure and low temperature infiltration for 4-10 h.

7. The preparation method according to claim 1, characterized in that: The supercritical fluid in step (5) is at least one of supercritical carbon dioxide and supercritical nitrogen.

8. The preparation method according to claim 1, characterized in that: The supercritical fluid foaming conditions described in step (5) are as follows: placing the foaming precursor obtained in step (4) into a molded foaming cavity, controlling the temperature at 140-160° C., injecting supercritical fluid at a pressure of 8-15 MPa, maintaining constant temperature and pressure for 1-4 h, then releasing the pressure to normal pressure, and opening the mold to obtain a foaming material.

9. A fluororesin microporous foam material, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Polyvinylidene fluoride resin expanded beads, and molded articles of polyvinylidene fluoride resin expanded beads

    CN102348745A

  • Polypropylene composite material for supercritical carbon dioxide foaming and preparation method of polypropylene composite material

    CN106987050A